Comparision of Various Non-Operative Treatment Modalities Available for Treatment of Cervical Spondylosis - Nishant Gaonkar, Kiran Gaonkar (International Journal of Advanced Science and Technology, 2020)
Introduction:The prime goal in the treatment of Cervical spondylosis is torelieve pain primarily an as early as possible and also allowspatients to perform their daily activities with an ease. Aim:We aim to compare the various non-operative treatment modalities available for treatment of cervical spondylosis. Material and Methods:This present crossectional and questionnaire based study included 150 patients diagnosed with Cervical spondylosis. We used mainly 3 types of nonoperative treatment measures. Based on this we divided our study sample into 3 study groups. Results:Mean age of the population in our study was 42.34 years. Females (57.33%) were seen to be more affected than males (42.66%) in our study.Out of total 150 patients, maximum score of 5 was seen in 19 patients of only group 3, while none of the other group patients reached the highest score of satisfaction. Over all on comparison, Group 3 showed the best results. Conclusion:We conclude that comparisons of nonsurgical treatment options in comparison to surgical interventions are important. Various non surgical approaches are available which would help in clinicaldecision making, when the primary outcome intention isto reduce pain, improve functional ability, return to work and prevent disability or impairment Keywords: Cervical spondylosis, non-operative, physiotherapy, analgesics